MUSIK BAND SEBAGAI MEDIA TERAPI PADA PENYANDANG AUTISME DI SLB NEGERI SEMARANG - petriana, rahel (Universitas Negeri Semarang, 2014)
Music as one of the areas that are closely related to human life has an effect on the healing of both physical and psychological (mental). This is manifested by the presence of music therapy in certain agencies, such as hospitals, homes, and special school. Students from special school are also referred to children with special needs (ABK) or diffable, one of which is autistic. Autism is a disorder with characterized by difficult social and tend to be isolated from others. Characteristics of band is collaboration, in which is the opposite characteristics with autism, that’s why research about band as treatment media for students with autism in State Special School of Semarang conducted. The result is the band chosen because it has the function of motion therapy, memory, and social. Models of music therapy in State Special School of Semarang are music therapy and music classes with the process of music therapy with class model’s using drill imitation.